Operating problems of buildings erected by using OWT large panel technology on the example of a ten-storey residential building in Rzeszów - Wróbel, Krystyna; Kubiszyn, Wiesław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article in general describes the problems- associated with maintenance of buildings erected in large panel technology and their importance. In particular, the issues of sustainability, safety and comfort of use of buildings erected in the OWT technology in the 80's and 90's were illustrated on the example of the last residential X-storey building built in this technology in Rzeszow, located in one of the housing estates. The building have been monitored by the authors of the paper since 2002. During that time many defects have been successively found and investigated. Proposed remedial solutions aimed at bringing the building to normal state as well as providing a sense of security and comfort to ensure a good technical state of the building and enhance the residents’ feeling of safety. Some of the solutions have already been implemented, but some are waiting for implementation in conjunction with a thermomodernisation.